The Relationship Between Macro-Nutrient Intake, Food Security, and Nutrition-Related Knowledge with The Incidence of Stunting in Toddlers - Nabilah, Khansa; Muhdar, Izna Nurdianty; Lestari, Widya Asih; Sariman, Sarina (Journal of Health and Nutrition Research, 2024)
Stunting is a condition of impaired growth in toddlers due to prolonged nutritional deficiencies. This issue is a significant global nutritional problem, particularly in poor and developing countries, including Indonesia. This study aims to examine the relationship between macronutrient intake, food security at the household level, and nutrition-related knowledge on the incidence of stunting among toddlers in the working area of Cimarga Health Center. This study employed a cross-sectional design. The sample size consisted of 99 toddlers from 11 villages within the Cimarga Health Center's jurisdiction. Analysis was conducted using the Chi-Square test. The findings reveal a stunting prevalence of 34.3% among toddlers. There is a significant relationship between household food security (p=0.014) and the incidence of stunting (OR=1.630; 95% CI=1.381-1.923). However, no significant relationships were found between energy intake (p=0.140), carbohydrate intake (p=0.544), protein intake (p=0.607), fat intake (p=0.439), and maternal nutrition knowledge (p=0.411) with the incidence of stunting in toddlers in the Cimarga Health Center area. This study underscores the importance of enhancing household food security as a primary strategy to reduce stunting despite the lack of significant relationships between macro-nutrient intake and maternal nutrition knowledge